2005
DOI: 10.1001/archneur.62.4.630
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Machado-Joseph Disease

Abstract: Machado-Joseph disease is an autosomal dominant spinocerebellar ataxia with expanded trinucleotide repeats. Although autonomic nervous system degeneration was documented in postmortem reports, the autonomic dysfunction in patients with Machado-Joseph disease, either in clinical analysis or electrophysiological investigations, has not yet been studied in detail. Methods: Fifteen patients with genetically confirmed Machado-Joseph disease and 34 healthy subjects were studied. The study design included a detailed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 18 publications
5
51
1
1
Order By: Relevance
“…In our study, however, HUT-induced BP and cerebral oxyhemoglobin did not fall except in one patient who showed neurally mediated syncope. In previous studies [5,6,12], the incidence of orthostatic hypotension was not extremely high in MJD patients (13-26%), as in our study, and this incidence seems relatively low in spite of the incidence of postural dizziness. A reduced initial HR response to arising suddenly and an excessive HR rise during HUT may account for the high incidence of postural symptoms without orthostatic hypotension.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In our study, however, HUT-induced BP and cerebral oxyhemoglobin did not fall except in one patient who showed neurally mediated syncope. In previous studies [5,6,12], the incidence of orthostatic hypotension was not extremely high in MJD patients (13-26%), as in our study, and this incidence seems relatively low in spite of the incidence of postural dizziness. A reduced initial HR response to arising suddenly and an excessive HR rise during HUT may account for the high incidence of postural symptoms without orthostatic hypotension.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies also indicated that postural symptoms were common (26-47%) in genetically diagnosed MJD patients [5,6]. In our study, however, HUT-induced BP and cerebral oxyhemoglobin did not fall except in one patient who showed neurally mediated syncope.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Sequeiros and Coutinho 4 reported difficulty in sphincter control in 5.8% of 143 Portuguese patients. The nationwide epidemiological survey in Japan 14 revealed voiding dysfunction in 31.3% of 66 patients, whereas Yeh et al 15 in Taiwan reported that 53% of their patients had urinary disturbance (nocturia and/or incontinence) and more than half of the patients had abnormal sudomotor function.…”
Section: Discussionmentioning
confidence: 96%